Manajemen Stres bagi Guru pada Masa Pandemi Covid-19 - Riswanti Rini; Diah Utaminingsih; Ratna Widiastuti; Yohana Oktariana (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
The outbreak of the Corona Virus Disease 2019 (Covid-19) pandemic since December 2019 until now requires all teaching and learning activities for students to be temporarily carried out at home. This needs to be done in order to minimize mass physical contact so that it can break the chain of spreading the virus. To fill the teaching and learning activities that must be completed in this academic year, the government has adopted a policy of learning to be carried out through distance learning using online media (on the network), either using a cellphone, PC, or laptop. Online learning that has been running, makes teachers also cause stress because of the large number of classes and students and demands from conditions or praxis that cause many problems. In an emergency situation, the teacher at that time had to act quickly so that learning could run effectively. Teachers need to be quick to take action and manage classes remotely. This includes managing materials and tasks of very short duration. In a short period of time there are obstacles that occur both from the side of the teacher and the students.When experiencing stress, the body will unconsciously manage stress. Management in dealing with stress is a way to increase his immunity to stress. Effective stress management will result in permanent adaptation, giving rise to new habits or improvements from old situations, while ineffective stress management will end up being maladaptive, namely deviant behavior and harm to oneself and others.